PENERAPAN METODE NUMBERED HEADS TOGHETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII PADA MATERI BELAH KETUPAT DAN LAYANG-LAYANG DI SMPN 2 MAYANG TAHUN PELAJARAN 2013/2014 - Tri Susilaningtyas (FKIP Universitas Islam Jember, 2015)
This study is aimed at investigating the increased activity and achievement of the students of SMPN 2 Mayang in the academic year 2013/2014 through the implementation numbered heads together (NHT) strategy. The research design employed in this study was classroom action research (CAR) that consists of cyclical procedures. The research findings show that the percentage of students’ learning activity in cycle 1 reached 90,7% and 92,2% in cycle 2. Whereas, the results of the average score of students daily test in cycle 1 was 81,78 and 83,06 in the cycle 2. In reference to the research findings previously described, it completely proved that the students’ activity and their achievement could be improved through the implementation of numbered heads together (NHT) strategy.Keywords: Cooperative learning, NHT, students’academic achievement.